Drain line clogs with a 1.6 gallon per flush water closet - Le, Rene (Kansas State University, 2015)
Typical building sanitary lines are sloped at a minimum of 1/8” to utilize gravity and prevent liquid separation from solid waste. The purpose of this research is to analyze how a lesser amount of water from a 1.6 gallon per flush water closet affects drainage in a four inch diameter pipe at 1/4" slope. Low flow water closet manufacturers ensure that waste clears the bowl, but there is no significant research following the flushed water further down the pipe line. This research utilizes a 1.6 gallon per flush floor-mounted water closet connected to 30 feet of sloped four inch PVC Drain Waste Vent piping. Data presented from 25 flush trials indicates that further research needs to be conducted at a smaller pipe diameter. Four-inch piping is too large, causing the 1.6 gallons of water to quickly lose the required force over the course of 30 feet, resulting in pipe line clogs. An average of four additional water-only flushes are necessary to completely clear the test media and toilet paper from the pipe. This research references previously published research and focuses on test results presented by the Plumbing Efficiency Research Coalition. Two case studies of city wide replacements of old water closets are presented to discuss the viability of city wide mandates in relation to water conservation.
Keywords: Plumbing; Plumbing Efficiency Research Coalition; Low Flow; Pipe Clogs; Architectural engineering (0462)